Reduction of Heavy Metal (Pb) ions in industrial waste using activated carbon based on used catalysts - Herawati, Netty; Ummi Kalsum, Rifdah,; Miftakhul Muthiah, Nyayu (International Journal of Scientific Research and Management (IJSRM), 2023)
Used catalyst-based activated carbon is activated carbon made from used catalysts from the crude oil cracking process. The used catalyst used is a type of crystalline Zeolite with a regular structure, which contains elements of Silica Oxide, Alumina Oxide, and Calcium Oxide. The use of organic activated carbon to treat waste has been widely used, the use of used catalyst waste as activated carbon is very potential because the catalyst used for oil company cracking is no longer used. Tofu industry is one of Indonesia's industries dominated by small-scale businesses with limited capital, so most tofu industries do not have waste treatment units, where liquid waste is directly discharged into sewers or water bodies without treatment first. Tofu industrial waste contains pollutants both organic and inorganic. Initial analysis of tofu industry liquid waste containing Pb metal. This study aims to determine the effect of mass variation and stirring time of used catalyst-based activated carbon adsorbent on reducing Heavy Metal Ions (Pb) in tofu industry liquid waste. The adsorption process is carried out with mass variations of activated carbon of 5, 10, 15, 20, and 25 grams. Stirring time variations are 30, 60, 90, 120, and 150 minutes. From the results of the study, it is known that the best condition for reducing Pb content was obtained at a stirring time of 60 minutes and a large catalyst-based activated carbon mass of 66.33%